2016
DOI: 10.1002/hyp.11073
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impacts of riparian buffer zones on sediment and nutrient loadings into streams at watershed scale using an integrated REMM-SWAT model

Abstract: Riparian buffer zones in agriculture dominated watersheds play important roles in reducing nonpoint source pollution into aquatic ecosystems and are widely used as a Best Management Practice. Assessment of the effectiveness of riparian buffer zones by modeling method is widely used for watershed management as field measurement-based assessment is difficult and expensive.The integration of Riparian Ecosystem Management Model (REMM) and Soil and Water Assessment Tool (SWAT) has been developed to simulate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Therefore, the restoration and maintenance of riparian ecosystem function has become a central and urgent need in geographical and ecological research [3]. At present, most researchers focus on the corridor [5], buffer [6] and revetment functions [7] of the riparian ecosystem, and carried 2 of 16 out studies on riparian structural features [8,9], biodiversity conservation and influencing factors [5], prevention and control of non-point source pollution [6] and riparian maintenance and soil erosion prevention [7,10,11]. However, compared to riparian biodiversity and agricultural non-point source pollution control mechanisms, soil erosion control of the riparian zone remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the restoration and maintenance of riparian ecosystem function has become a central and urgent need in geographical and ecological research [3]. At present, most researchers focus on the corridor [5], buffer [6] and revetment functions [7] of the riparian ecosystem, and carried 2 of 16 out studies on riparian structural features [8,9], biodiversity conservation and influencing factors [5], prevention and control of non-point source pollution [6] and riparian maintenance and soil erosion prevention [7,10,11]. However, compared to riparian biodiversity and agricultural non-point source pollution control mechanisms, soil erosion control of the riparian zone remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Water diversion to control pollution was originally a lake purification technology, and there are many application examples with lake eutrophication. After the recovery, Black Brook in Canada had a sediment retention rate of 29.4% to approximately 74.07%, an N reduction rate of 9.61% to approximately 57.85%, and a P reduction rate of 18.61% to approximately 68.12% (Zhang C et al 2017). Yin et al (2018) calculated the environmental flows under different HC (high, medium, low) scenarios through consideration of water purification and ecological water demand and applied them to the Shili River, China.…”
Section: Summary Of Restoration Strategies For Wetland System Hcmentioning
confidence: 99%
“…Shan et al (2014) determined the optimal width of the vegetation strip that assured clean water in reservoirs that varied with the type of soil and topography. Zhang et al (2017) assessed the effect of the size of sub-basin partition on modeling and identified a reduction in sedimentation rate from 74.07% to 29.4%, due to riparian buffers, among the eight subwatersheds they studied. Moriasi, Steiner and Arnold, (2011) found that applying a riparian forest buffer only and a combination of a riparian forest buffer and filter strip buffer simultaneously resulted in a reduction in suspended sediment concentration by 68% and 72%, respectively.…”
Section: Introductionmentioning
confidence: 99%